Universal Plug and Play Machine Models: Modeling with Distributed Abstract State Machines - Glässer, Uwe; Veanes, Margus (Design and Analysis of Distributed Embedded Systems, IFIP 17th World Computer Congress (DIPES 2002), 2002)
We present a high-level executable specification for the Universal Plug and Play (UPnP) standard illustrating the use of Abstract State Machine (ASM) technology as a practical tool for applied systems engineering. The concept of distributed real-time ASM allows us to combine both synchronous and asynchronous execution models in one uniform model of computation.